Synthesis of Low-Cost Adsorbent Based on Fly Ash for Heavy Metal Reduction of Cu and Cr In Textile Industrial Liquid Waste - Mulyatun Mulyatun (Faculty of Science and Technology, Universitas Islam Negeri Walisongo Semarang, 2018)
Heavy metal copper (Cu (II)), Chromium (Cr (IV) is a heavy metal that dominates textile industrial wastewater. Too large concentrations of Cu (II) in water can cause poisoning which has side effects of liver damage and gastrointentinal disorders. Cr metal in the body will cause interference with DNA synthesis and increase mutagen changes that can cause tumors. The use of fly ash as a Low Cost Adsorbent is an alternative. The research method used is a physical activation process with carbonization at high temperatures (300˚C, 400˚C and 500˚C) in the furnace to be continued with chemical activation using concentrated acids (H2SO4 and CH3COOH) or base (KOH) in fly ash. Morphological analysis and the synthesized adsorbent function groups were performed using Scanning Electron Microscopes (SEM) and FTIR. Based on the adsorption capacity test, the ability of fly ash to adsorb Cu metal waste was 0.9962 mg/g and for Cr metal was 0.4760 mg/g. The temperature increase on the physical activation of fly ash (300 0C, 4000C, 5000C) causes an increase in the adsorption capacity of the synthesized fly ash. The best adsorbent for Cu metal is A5K with an adsorption capacity of 0.9994 mg/g under optimal conditions. The best adsorbent for Cr metal is A5S with an adsorption capacity of 0.9325 mg/g under optimal conditions. ©2018 JNSMR UIN Walisongo. All rights reserved.